Acute Flaccid Myelitis in German Children in 2016—the Return of Polio? - Hübner, Johannes (Dtsch Arztebl Int, 2017)
BACKGROUND: Although poliomyelitis has almost been eradicated worldwide, cases of a polio-like disease with asymmetrical flaccid paralysis of variable severity have been seen repeatedly in recent years. METHODS: Data were collected on children treated in hospitals in the German federal states of Bavaria and Lower Saxony in 2016. The frequency of disease across Germany was estimated on the basis of voluntary reporting to the Robert Koch Institute. 16 cases were registered there for the entire year 2016. RESULTS: 7 children with flaccid paralysis of acute onset were treated in the participating hospitals in the summer and fall of 2016. We describe two illustrative cases, one with a mild course and one with a severe course. Rapid diagnosis requires not only clinical neurological assessment but also neurophysiological studies, magnetic resonance imaging (MRI), and targeted microbiological testing. The characteristic features include damage to the anterior horn of the spinal cord that can be seen on MRI and/or electrophysiologically demonstrable abnormalities indicating motor neuron damage. A pathogen can hardly ever be identified in the cerebrospinal fluid, but the epidemiological context and the detection of viruses in the stool or respiratory secretions indicate that enteroviruses may be responsible. CONCLUSION: The prognosis of this disease cannot be reliably assessed at first, and no specific treatment is currently available.